Adenosine deaminase acting on RNA 1 (ADAR1) as crucial regulators in cardiovascular diseases: structures, pathogenesis, and potential therapeutic approach - Chen, Jieying; Jin, Junyan; Jiang, Jun; Wang, Yaping (Frontiers in Pharmacology, 2023)
Cardiovascular diseases (CVDs) are a group of diseases that have a major impact on global health and are the leading cause of death. A large number of chemical base modifications in ribonucleic acid (RNA) are associated with CVDs. A variety of RNA modifications exist in cells, among which adenosine deaminase-dependent modification is one of the most common RNA modifications. Adenosine deaminase acting on RNA 1 (ADAR1) is a widely expressed double-stranded RNA adenosine deaminase that forms inosine (A-to-I) by catalyzing the deamination of adenosine at specific sites of the target RNA. In this review, we provide a comprehensive overview of the structure of ADAR1 and summarize the regulatory mechanisms of ADAR1-mediated RNA editing in CVDs, indicating ADAR1 as a promising therapeutic target in CVDs.